La idea de filosofía en Ortega y Gasset - RUIZ FERNÁNDEZ, Jesús (Revista de Filosofía, 2010)
This article does a research into a theme that has not been studied specifically. This is curious, as the idea of philosophy is the most important one in Ortega y Gasset’s system. Here, it is considered concerning its specifity: the principles of pantonomy and autonomy his platitudinous nature and its integrating and critical functions. As it can be seen, Philosophy’s traditional characteristics. Ortega sets them out in a masterly way, reaching its hight literary brilliance when he praises Philosophy.
Keywords: Principle of pantonomy; Principle of autonomy; Platitude; Integrataing function; Critical function